Pendidikan Anti Korupsi untuk Guru-Guru Sekolah se-Salatiga dan Sekitarnya - Sri Harini Dwiyatmi; Setyo Pamungkas; Selvie Novitasari; Belby Sahyang Binela; Rachel Angeline Saragih (Jurnal Hukum Lex Generalis, 2024)
The purpose of community service with the title is to understand the important role and strategy of school teachers in instilling anti-corruption. so that teachers can be agents of change in their schools for anti-corruption. After a long time moving for students, teachers play a strategic role. Because teachers are continuously in schools. To measure how much teachers understand anti-corruption for younger generation for a new sky and a new earth in the future that is free from corruption. from the pre-test it is known that only about 10% of teachers have received material on anti-corruption and have anti-corruption activities in schools that continue to exist until now and only a few are no longer there. What already exists in schools must be maintained and developed while continuing to motivate teachers / schools that do not yet have anti-corruption activities. Anti-corruption education in this city with a game model obtained from the Indonesian KPK-SPAK is indeed new. Anti-corruption models with games must continue to be developed together with new partners, the regional inspectorate of this city is valuable, especially in the post-test participants were known to get new ideas to carry out and develop anti-corruption, even though the school curriculum has not accommodated it.